Rhizophora apiculata Kombucha Fermented Beverage: Secondary Metabolite Content and Antioxidant Activity - Agustina Monalisa Tangapo; Susan Marlein Mambu; Parluhutan Siahaan; Erika Kolompoy; Marsia Pasassa (Jurnal Penelitian Pendidikan IPA, 2026)
Kombucha is a functional beverage produced by the fermentation of bacteria and yeast (SCOBY). This fermented beverage contains various bioactive compounds with antioxidant potential. Rhizophora apiculata is a mangrove plant that contains bioactive compounds with rich health benefits. Based on this, modifying kombucha fermentation with a mangrove leaf tea substrate can increase kombucha's effectiveness as an antioxidant. This study aims to analyze the secondary metabolite content profile and antioxidant activity of R. apiculata kombucha. Kombucha fermentation was carried out for seven days with a 10% sugar concentration. Analysis of the secondary metabolite content profile of R. apiculata kombucha was carried out using GC–MS analysis. Antioxidant activity was evaluated using the DPPH assay. The results showed a decrease in pH during the fermentation period and an increase in total acidity. The results of GC–MS analysis of R. apiculata kombucha showed 23 secondary metabolite compounds with varying retention times, area sizes, and chemical structures. The composition of the identified compounds was dominated by acetic acid (26.9%), 5-hydroxymethylfurfural (HMF, 12.38%), N′-(diaminomethylidene) butanehydrazide (7.68%), 1,2,3-propanetriol, 1-acetate (6.91%), and methyl α-D-rhamnopyranoside (5.12%). R. apiculata kombucha has the potential to act as an antioxidant, with an IC₅₀ value of 27.16 ppm, which is classified as a very strong antioxidant.